HUBUNGAN MEKANIKA TUBUH DENGAN KEJADIAN LOWBACK PAIN PADA PERAWAT RUANG ICU DAN HCU RUMAH SAKIT AWAL BROS BATAM - Utari Christya Wardhani (Menara Ilmu, 2018)
The daily nurse's job is to provide care to patient especially in lifting, moving, pushing, orattracting the patient to position their bed rest. Factors that can cause back injuriesinclude the presence of body position that is not true for example in the process of movingpatients. The result of preliminary survey conducted by the researcher to the room nurse atRS Awal Bros Batam through questionnaire, 82 questionnaires, obtained result of 35nurses (42,6%) had experienced Lowback pain during work, with the highest number ofLBP incidence in HCU and ICU ( 16.8%) are generally complaints that occur after takingaction to lift, push, move, and care for the patient. This study aims to determine therelationship of body mechanics with the incidence of low back pain on nurses HCU roomand ICU Awal Bros Batam Hospital. This research uses descriptive method with crosssectional approach. The sample in this research is all nurses of ICU and HCU room RSAwal Bros Batam 2017 which amounted to 31 people. This research instrument uses theNordic Body Map Questionnaire to find out back pain complaints and REBA checks toassess LBP risk work posture. The results showed that the prevalence of LBP severe painis high enough in ICU and HCU nurses RS Awal Bros Batam 2017 (67.7%). Statistical testresults obtained value ρ = 0,000 which means the value of sig ρ <0.05. This study leads tothe conclusion that there is a significant relationship between body mechanics with theincidence of lowback pain on ICU nurses and HCU RS Awal Bros Batam. It is expectedthat ICU and HCU nurses can reduce low back pain complaints by working according toproper work posture (body mechanics) that is not too bent at work, resting on both legs,and doing less flexion movements at other corners of the body.Keywords: Body Mechanic, Lowback Pain, Nurse